The infrared spectrum of NaV₃P₃O₁₂ - Baran, Enrique José (1990)
Materials belonging to the α-CrPO₄ structural type are rather uncommon. Only two simple compounds, apart from α-CrPO₄ itself [1, 2], are known to adopt this structure, namely CrAsO 4 [3] and RhPO₄ [4]. A phase of composition NaV₃P₃O₁₂ (with chemical formula NaVllV₂III nP₃O₁₂) has recently been prepared [5]. It possesses a packed structure of α-CrPO₄, with the Na + cations located in the tunnels of the α-CrPO4 framework. It seems, therefore, interesting to characterize this new material by means of infrared (IR) spectroscopy in order to obtain an insight into the vibrational behaviour of this complex and unusual mixed-valence compound. The investigated samples were obtained as described in [5]. The IR spectra were recorded with a Perkin-Elmer 580B spectrophotometer, using the KBr pellet technique.